STRATEGI GUEST SERVICE AGENT DALAM MEMAKSIMALKAN EFEKTFITAS KERJA DI HOTEL ROYAL AMBARRUKMO YOGYAKARTA - Rahman, Akh Fajar; Sukarni, Sri; Mafuah, Hanni (AKPARDA, 2023)
This study aims to find out what efforts are made by guest service agents in maximizing the effectiveness of work in the front office department, this research was conducted using qualitative methods. Data collection techniques using interviews, observation, documentation and literature study. The results showed that to maximize performance in the guest service section at the Royal Ambarukmo Yogyakarta hotel, several strategies were implemented, namely 1. Utilization of human resources, 2. Adequate finances to support operations, 3. Complete and adequate equipment, 4. Methods , 5. Engine